The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1177/0163443718818363
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of live streaming and Twitch.tv on the video game industry

Abstract: This article explores the growing importance of live streaming, specifically on website and platform Twitch.tv, to the games industry. We focus not on live streaming as a form of media production and consumption, but instead explore its newly central role in the contemporary political economy of the whole video games ecosystem. We explore three cases: streaming newly released games and the attendant role of streaming in informing consumer choice; the visibility and added lifespan that streaming is affording to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 34 publications
(29 reference statements)
1
59
0
5
Order By: Relevance
“…Video game streaming services have become an important source of information. Johnson and Woodcock [ 55 ] show their impact on the entire video game ecosystem and industry, revealing how they help build links between video game developers and streamers. Streaming platforms influence players’ expectations regarding new releases, with users going to these platforms as an audience member to find out information, to see how new releases are tested live or how older titles are updated, or to watch indie game releases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Video game streaming services have become an important source of information. Johnson and Woodcock [ 55 ] show their impact on the entire video game ecosystem and industry, revealing how they help build links between video game developers and streamers. Streaming platforms influence players’ expectations regarding new releases, with users going to these platforms as an audience member to find out information, to see how new releases are tested live or how older titles are updated, or to watch indie game releases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The factors linked to the risk or opportunity arising from the consumption of live video game streaming may be heterogeneous among individuals [ 19 ]. Previous research has primarily focused on the positive or negative aspects associated with the rise of this new phenomenon [ 18 , 20 , 21 , 22 ], but no studies to date have identified user groups or differences between them and their perceptions. As Jeong, et al [ 19 ] point out, the identification of homogeneous subgroups can contribute to a better understanding of gaming and viewing behaviour.…”
Section: Introduction and State Of The Researchmentioning
confidence: 99%
“…Based on recent research in terms of user-attraction and interest on social media (Liu et al, 2014;Salganik et al, 2006;Venkatanathan et al, 2012;Wen & Lin, 2010), paired with contemporary trends in online gaming, particularly in the streaming platform of Twitch.tv (Johnson & Woodcock, 2019a, 2019bWoodcock & Johnson, 2019), the aim of the present was to discover user-attraction characteristics of different posted content on the Facebook brand page of a Hungarian Twitch.tv streamer, RandomNickname.…”
Section: Resultsmentioning
confidence: 99%
“…Twitch. tv, according to Johnson and Woodcock (2019), is having a particular impact on the video game industry, in terms of extending the visibility and lifespan of games, offering opportunities for game reviews and spreading knowledge and expertise in game programming as well (Johnson & Woodcock, 2019b).…”
Section: Introductionmentioning
confidence: 99%